Effects of Tire Pressures and Test Temperatures on Permanent Deformation of Direct Coal Liquefaction Residue Mixture - Zhi, Suo; Jie, Ji; Ran, Zhang; Zhe, Wang; Hui, Yao; Dongzhao, Jin (Frontiers in Materials, 2020)
This main objective of this research is to investigate the permanent deformation of the asphalt mixtures added direct coal liquefaction residue (DCLR) under various tire pressures and temperatures. Three types of asphalt mixtures, including control/DCLR /composite-DCLR modified asphalt mixture, were prepared by the Marshall design procedure. The rutting test was conducted under various tire pressures changing from 0.7 MPa to 1.0 MPa with a 0.1 MPa interval and at temperatures varying from 55oC to 70oC with a 5 oC interval. Moreover, the dynamic stability and rutting depths were obtained to evaluate the resistance of permanent deformation withthree types mixtures. It was found that the rutting resistance of three mixtures declines with the increased tire pressures and temperatures at various rates. The mixture containing DCLR present has a lower rutting depth and higher dynamic stability compared to the control group asphalt mixture under the conditions. Furthermore, the rutting resistance of composite-DCLR added asphalt mixture is better than that of DCLR modified asphalt mixture. It indicates that the DCLR is favorable for the improvement of rutting resistance. Moreover, the ANOVA was applied, in which analysis results showed that the parameter of the temperature is more sensitive than the tire pressure. Based on the least square procedure, the relationship between dynamic stability and rutting depths is obtained, and the accuracy of the prediction is acceptable.